CBCT as a novel pre-op non-invasive method to determine the location of Greater Palatine Foramen - Usman Manzoor Warraich, Maha Maqbool, Sittara Javed, Khurram Ataullah, Zubair Ahmad Khan, Asad Mahmood, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the greater palatine foramen position with reference to Maxillary molar teeth among patients presenting in a tertiary care hospital in Lahore by using cone beam computed (CBCT). Method: In this cross sectional studywhich was conducted at Fatima Memorial Hospital located in Lahore, in which a total of 80 patients were included. Informed consents and demographic details were noted. Cone beam computed tomography was taken in Planmeca Promax 3D Mid (60-120 kV; 9-33 s; 200 um voxel size) of all subjects. As per operational definitions, linear measurements for location of greater palatine foramen were measured. All the information was recorded in a specifically designed form. Results: Onaveragethe age ofpatients in this study was 39.35±11.19 years, 38(47.50%) patients were male. On left and right side the most common position was between middle and mesial face of third molar noted in 45(56.25%) and 43(53.75%) patients respectively. Conclusion: The most common position both sides was the position between middle and mesial face of third molar followed by position between distal face and middle of third molar in patients reporting in a tertiary care hospital located in Lahore by using cone beam computed tomography (CBCT) Keywords: Greater palatine foramen, cone beam, CT,